Influence of attachment theory on hotel service for specific customers. Issue 1 (2nd January 2017) - Tran, Xuan; Barbosa, Daniel; Maisel, Jonathan; Zedonek, Jonathan
Abstract: Specific strategies for hotel brand quality development are demonstrated based on the attachment theory. Customers are identified by their levels of anxiety and avoidance. The study used a random sample of 376 U.S. hotel guests in 2013 to test the hotel brand attachment model. The study found that (1) emotional attention with discounted price is most important for guests with base hotel membership; (2) prompt service with discounted price within a time limit is for guests with no hotel membership at a midscale hotel; (3) safety and accuracy service with a full price is for guests with no hotel membership at a luxury hotel; and (4) best performance with a full price is for guests with elite hotel membership.